2004
DOI: 10.1007/s12110-004-1007-7
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive cooperation

Abstract: Cooperation can evolve in the context of cognitive activities such as perception, attention, memory, and decision making, in addition to physical activities such as hunting, gathering, warfare, and childcare. The social insects are well known to cooperate on both physical and cognitive tasks, but the idea of cognitive cooperation in humans has not received widespread attention or systematic study. The traditional psychological literature often gives the impression that groups are dysfunctional cognitive units,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…For example, the stepwise transition to the foraging niche increased interdependence and reliance on cultural transmission, causing stronger pressure for cooperation and collective problem solving. We propose that the result was the evolution of more sophisticated collective intelligence and shared intentionality [ 3 , 7 , 8 , 11 ]. While those cognitive abilities had often been described as causes of human culture from a mechanistic or proximate perspective, they are ultimate consequences of the selective pressures for cumulative culture in the foraging niche.…”
Section: Discussion: Gene-culture Coevolution and Human Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the stepwise transition to the foraging niche increased interdependence and reliance on cultural transmission, causing stronger pressure for cooperation and collective problem solving. We propose that the result was the evolution of more sophisticated collective intelligence and shared intentionality [ 3 , 7 , 8 , 11 ]. While those cognitive abilities had often been described as causes of human culture from a mechanistic or proximate perspective, they are ultimate consequences of the selective pressures for cumulative culture in the foraging niche.…”
Section: Discussion: Gene-culture Coevolution and Human Evolutionmentioning
confidence: 99%
“…Human cumulative culture [1][2][3][4][5][6] differs from the culture in other primates in that it more extensively accumulates over generations without loss, a property described as directional or 'ratchet' effect [7]. Human culture extends across multiple minds [8][9][10][11] and generally cannot be recreated from scratch [12]. While chimpanzees present cultural traditions and instances of teaching [6,13], evidence of cultural ratcheting beyond three-part tools is so far absent [14].…”
Section: Introductionmentioning
confidence: 99%
“…Individuals may have begun benefitting from trade based on the appearance of specialization, which in turn is linked to the number and complexity of learned skills needed in daily life. Alternatively, it is possible that at some stage, owing to the establishment of cooperative breeding [100], joint innovation became favoured [101].…”
Section: How About Our Ancestors?mentioning
confidence: 99%
“…However, in the collaborative experiment, participants' PPS were more symmetrical. In social psychology, it has been observed that individuals involved in a group sometimes think and act in a way that seems logical at the group level while appearing irrational, even detrimental, at the individual level [47,48]. Similar phenomena could also be present at the level of sensory integration near the body where the seemingly disadvantageous symmetrical remapping of PPS could actually be beneficial for group behaviour.…”
Section: Discussionmentioning
confidence: 99%